Ultrasonography and CT of the vas deferens in a neutered male dog with chronic exogenous estrogen exposure. Issue 4 (29th March 2022) - Harris, Olivia S.; Eitzer, Andrew D.; Saver, Alexander; Sample, Susannah J.; Loeber, Samantha J.
Abstract: A 2‐year‐old male neutered Rat Terrier was presented for alopecia, recurrent urinary tract infections, and urinary incontinence. Abdominal ultrasound and CT identified a thin, tubular, paired structure arising from the craniodorsal aspect of an enlarged, cystic prostate. An atypical uterus masculinus was initially suspected, however it was then identified that the patient had chronic exogenous estrogen exposure, and surgical resection and histopathology was consistent with an enlarged and inflamed vas deferens. Vas deferens enlargement and vasitis secondary to chronic hyperestrogenism should be considered for a tubular, paired structure arising from the craniodorsal prostate in a male dog.